Media for sex education in elementary school: Which one is better? - Maharani, Luluk Nandya; Sanyata, Sigit (Research and Social Study Institute, 2019)
In the last decade, the problem of child sexual violence is very prevalent, therefore the need for the application of sex education in elementary school children. This is done to provide knowledge about sex education that is tailored to the stage of child development and to avoid the danger of predators of violence and sexual abuse. Providing knowledge about sex education will be better if there are supporting media in its delivery. Regarding the good media in teaching sex education to elementary school children there are currently two namely electronic and print media. Although there are two media to introduce sex education, but they have not shown maximum results, both media have their advantages and disadvantages. This paper aims to review the literature in the delivery of sex education in elementary schools using electronic and print media. The results or reviews in this discussion are expected to provide information that can be used as a theoretical and methodological basis for further research in the use of sex education delivery media for elementary students.